VOCABULARY DEVELOPMENT OF KINDERGARTEN STUDENTS OF APPLE TREE PRE-SCHOOL SAMARINDA BY USING FLASHCARDS - Nadia Mustika Rachmita (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2016)
Abstract:This present study aimed to investigate 14 kindergarten students of Apple Tree pre-school Samarinda with various ability toward their English vocabularies development by flashcards. A Class Action Research was applied in this study. The data was collected through observation checklist, sequence of cycles and interview transcript. Then, building on the analysis of the collected data, it further discusses the vocabulary development of YL and provides suggestions for TEYL. This study revealed that; (1) most of the students developed their English vocabularies gradually by flashcards. (2) These result indicated that TEYL especially kindergarten students by using flashcards could give significant vocabularies development in learning process. Flashcards is one of the simplest and effective teaching materials for teaching YL vocabulary due to the fact that flashcards are categorized based on themes with full colored pictures which attractive for YL. As this study showed the students were engaged with the topics given since the teachers used flashcards to teach English vocabulary. It was difficult to make engagement with YL in English teaching and learning because YL have different mood, self-motivation, and self-confidence which influenced to the willingness in grasping the lesson. Finally, through this based-picture learning, the students indicated that their progress in vocabulary development although this phenomena was commonly happened in TEFL for YL that lead to teaching method done by English teachers who are required to do more innovation toward their teaching method, to develop sufficient knowledge and to use proper teaching media.